Poetry as Antidote to Toxic Certainty - Kershaw, Matt (Lumen et Vita, 2019)
In examining the discursive environment surrounding the Great War (1914-1918), one finds a familiar reduction of reality into flat and mutually exclusive binaries written in what Robert Graves called "Newspaper Language." In this article, I suggest such discursive flattening to be both unproductive and dehumanizing, employing the term "toxic certainty" to refer to language used by a given partisan over and against the perceived other, where the rhetorical force of an assertion is taken to be the proof of that assertion. To counter dehumanizing discourse both in and out of the pulpit, I suggest a remedy in an alternate reading of James 1:22, where preachers can aspire to be "poets of the word," rather than just self-deceiving hearers. This idea is developed through an examination of the poetic efforts to humanize the full reality of the Great War undertaken by Wilfred Owen and Siegfried Sassoon.